2020
DOI: 10.3390/ijerph17165762
|View full text |Cite
|
Sign up to set email alerts
|

Planning for Supportive Green Spaces in the Winter City of China: Linking Exercise of Elderly Residents and Exercise Prescription for Cardiovascular Health

Abstract: The elderly population have a high incidence of cardiovascular disease and are the main users of green spaces, such as city parks. Creating supportive green spaces for exercise for the elderly is of great significance to promote their cardiovascular health. The winter cities have a severely cold climate and high incidence of cardiovascular disease, while the elderly, especially those with cardiovascular disease, face more challenges when participating in exercise in the green spaces. In the context of the wint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 53 publications
(70 reference statements)
0
0
0
Order By: Relevance
“…Zeng et al found that cold weather significantly increases the risk of disability and even mortality among older adults during daily activities after analysing the data of demographic characteristics, and the socioeconomic and environmental information of the elderly in 22 provinces of China [45]. In addition, Leng et al explored the relationship between green spaces, facilities allocation and cardiovascular health in winter in the cold city of Harbin, China, and showed that environmental factors have a significant influence on health levels in harsh climates [46]. They also obtained similar conclusions by analysing the relationship between the ground covered with snow, outdoor activities and cardiovascular exercise prescription of elderly residents [47].…”
Section: Introductionmentioning
confidence: 99%
“…Zeng et al found that cold weather significantly increases the risk of disability and even mortality among older adults during daily activities after analysing the data of demographic characteristics, and the socioeconomic and environmental information of the elderly in 22 provinces of China [45]. In addition, Leng et al explored the relationship between green spaces, facilities allocation and cardiovascular health in winter in the cold city of Harbin, China, and showed that environmental factors have a significant influence on health levels in harsh climates [46]. They also obtained similar conclusions by analysing the relationship between the ground covered with snow, outdoor activities and cardiovascular exercise prescription of elderly residents [47].…”
Section: Introductionmentioning
confidence: 99%